Size and Sex Effects on Storm-Petrels’ Maximum Load-Lift at Takeoff - Alejandra Cano-Franco; Misael Daniel Mancilla-Morales; Araceli Contreras-Rodríguez; José Juan Flores-Martínez; Zulema Gomez-Lunar; Enrico Alejandro Ruiz (Diversity, 2025)
In the Gulf of California, seabirds carry heavy loads to feed their chicks, making their takeoff capacity crucial for foraging. While some studies explore this, few consider the lift force, induced power, or aerobic vs. anaerobic performance. Moreover, the differences between individuals—such as size or sex—remain largely unexamined, leaving gaps in the understanding of seabird flight efficiency. In this work, the load capacity during takeoff of the Least Storm-Petrel (LSP) and the Black Storm-Petrel (BSP) in Isla Partida Norte, Gulf of California, was analyzed. Forty-nine individuals of the Least Storm-Petrel group and 23 of the Black Storm-Petrel group were evaluated. In both species, the carrying capacity was found to be independent of individual size, but the Least Storm-Petrel managed to take off with a higher proportion of its total mass than the Black Storm-Petrel. Although smaller, LSPs lift more than BSPs, and environmental factors like El Niño also influence seabird performance. This study found that both storm-petrel species were smaller and lighter than previously reported; yet, LSPs carried relatively heavier loads than BSPs. Although BSPs had higher absolute values for mass and lift, LSPs were more energy-efficient. The muscle mass proportions were similar and typical for takeoff. No significant sex-based differences were found. Both species used aerobic and anaerobic takeoff, with anaerobic flight likely being more efficient.